Pembangunan Infrastruktur Pertanian dan Sosial Dalam Rangka Mempersiapkan Selopamioro Mandiri Sejahtera Berbasis Potensi Lokal - Sarmin Sarmin; Irkham Widiyono; Slamet Widiyanto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
Tis program aims to develop agricultural infrastructure and social culture for Selopamioro empowering and prosperous based on local potential. Te priority of  frst year programs were development of water reservoir in Kalidadap 2 and Srunggo, smart home fnishing in Srunggo 1, processed cashew as jam and shredded, promotion assistance in Bantul Expo event, branding and packaging innovation for cashew, to initiate government licensing, and develop standar operating procedure in processed cashew. All of programs as baseline to holistic development in Selopamioro based on local potential.